Fiscal Policy in Nigeria : Any Role for Rules? - Baunsgaard, Thomas (Washington, D.C. : International Monetary Fund, 2003)
Fiscal policy in oil-producing countries can be profoundly affected by oil revenue uncertainty and volatility. Policy formulation should factor in the exhaustibility of the natural resources and aim at reducing oil revenue volatility passed on to the economy. Past fiscal policy in Nigeria has not been successful in this regard, since both revenue and expenditure have been highly volatile, to a large extent reflecting oil price developments. The paper discusses the role an appropriately designed fiscal rule, nested within the long-run sustainable use of oil revenue, could have in providing a more stable framework for fiscal policy formulation. It also highlights practical implementation and transitional issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet